The mid-crustal architecture of a continental arc - a transect through the South Central Zone of the Pan-African Damara Belt, Namibia - Anthonissen, Christoffel Jasper (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Earth Sciences))--University of Stellenbosch, 2010.